Penjadualan pengeluaran menggunakan aturan pelepasan berprioriti dalam sistem bergangguan - Joesni Ralin, Ayu Bidiawati (2004)
This research address a problem faced by manufacturing companies that is the problem of production scheduling experiencing disruption. The disruption might be caused by changes of priority, new order, and changes of due date in production scheduling. Therefore, the scheduling have been created becomes disturbed. The production scheduling strategies investigated are Priority Dispatching Rules, i.e. (a) First Come First Served (FCFS), (b) Earliest Due Date (EDD), (c) Shortest Processing Time (SPT) and (d) Longest Processing Time (LPT), and are based on non-preemption scheduling and preemption scheduling. Simulation modeling is employed to find out the best strategy out of the four strategies mentioned. The research starts with a case study of production scheduling of a particular company and the understanding of its system's requirements. A basic model was developed from the case study as base of experimentation, evaluation and validation of the simulation model. Then this model is used as the basis in the application of the prioritized dispatching rules of non-preemption scheduling and preemption scheduling system. The basic model is then modified to simulate the preemption production scheduling system. Experiments on the models are conducted and analyzed. The simulation results show that Earliest Due Date (EDD) is the best among the prioritized dispatching rules. The Earliest Due Date (EDD) is also the best rules to do rescheduling for scheduling of non-preemption and scheduling of preemption.